Novel Evaporation Process for Deposition of Kesterite Thin Films Synthesized by Solvothermal Method - J. A. Estrada-Ayub; L. Álvarez Contreras; M. Román Aguirre; J. G. Murillo Ramírez; M. T. Ochoa-Lara; P. Pizá-Ruiz; A. Aguilar Elguezabal (Advances in Materials Science and Engineering, 2017)
Kesterite, a quaternary compound of Cu2ZnSnS4, is a promising option as a material absorber to reduce the cost of photovoltaic solar cells. The solvothermal method is a way to synthesize nanoparticles of this material. In this work, once synthesized, particles were deposited on a substrate through evaporation, and their morphological, structural, and optical properties were studied. Results show that changes of precursor ratios during solvothermal synthesis result in a modification of particle morphology but not on its size. The deposition of already synthesized kesterite through evaporation preserves kesterite structure and permits the formation of a homogenous film on a substrate. Optical reflectance and transmittance measurements allowed estimating the band-gap energy between 1.41 and 1.46 eV for representative samples, which is near the optimum for the absorber material.